Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Osmotic stress induces gut microbiota community shift in fish - Keng Po Lai; Xiao Lin; Nathan Tam; Jeff Cheuk Hin Ho; Marty Kwok‐Shing Wong; Jie Gu; Ting Fung Chan; William Ka Fai Tse (Environmental Microbiology, 2020)
Summary Alteration of the gut microbiota plays an important role in animal health and metabolic diseases. However, little is known with respect to the influence of environmental osmolality on the gut microbial community. The aim of the current study was to determine whether the reduction in salinity affects the gut microbiota and identify its potential role in salinity acclimation. Using Oryzias melastigma as a model organism to perform progressive hypotonic transfer experiments, we evaluated three conditions: seawater control (SW), SW to 50% sea water transfer (SFW) and SW to SFW to freshwater transfer (FW). Our results showed that the SFW and FW transfer groups contained higher operational taxonomic unit microbiota diversities. The dominant bacteria in all conditions constituted the phylum Proteobacteria , with the majority in the SW and SFW transfer gut comprising Vibrio at the genus level, whereas this population was replaced by Pseudomonas in the FW transfer gut. Furthermore, our data revealed that the FW transfer gut microbiota exhibited a reduced renin–angiotensin system, which is important in SW acclimation. In addition, induced detoxification and immune mechanisms were found in the FW transfer gut microbiota. The shift of the bacteria community in different osmolality environments indicated possible roles of bacteria in facilitating host acclimation.

Characterization of a new phage, termed ϕA318, which is specific for Vibrio alginolyticus - Ying-Rong Lin; Chi-Wen Chiu; Feng-Yi Chang; Chan-Shing Lin (Archives of Virology, 2012)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Role of the DxxDxD motif in the assembly and stability of betanodavirus particles - Yi-Min Wu; Chi-Hsin Hsu; Chun-Hsiung Wang; Wangta Liu; Wei-hau Chang; Chan-Shing Lin (Archives of Virology, 2008)